Conceptualization of Positive Evaluation in the Old English Poetry - Soloviova, Olha (Studia Philologica, 2025)
The study of axiological semantics in linguistics has traditionally focused on synchronic analysis, which has limited the understanding of the dynamics in the development of evaluative concepts. Previous works have largely concentrated on modern languages and their functional styles, failing to provide a comprehensive picture of how evaluativity was formed from a historical perspective. This article is based on the conclusion that diachronic analysis is critically important for understanding the evolution of evaluative categories, and it aims to model the conceptual structure of positive evaluation in Old English poetry. The research objective is to construct a diachronic-conceptual model of positive evaluation using Old English poetry, which will allow for the identification of key semantic components and their evolution. To achieve this, a list of 26 adjectives that verbalize positive evaluation was compiled. The main results of the study include the modeling of a frame-and-slot structure for the concept of GOOD, which consists of five key semantic slots: INTERNAL QUALITY, SOCIAL STATUS, FUNCTIONAL COMPETENCE, EXCEPTIONALITY, and UTILITARIANISM. The analysis confirmed that the concept of positive evaluation in Old English is anthropocentric, multifaceted, and based on moral, social, physical, and functional qualities. It was established that dictionary definitions mostly correspond to contextual usage, though some lexemes exhibit pragmatic variability, which points to the dynamic nature of evaluation. The conclusions confirm that the conceptual model of positive evaluation in Old English poetry is formed on the basis of etymological roots that originally denoted specific physical actions and phenomena and later acquired a more abstract meaning. This demonstrates that evaluative concepts are not static but are the result of gradual evolution, reflecting changes in the social system of values.